2017
DOI: 10.1111/gbb.12421
|View full text |Cite
|
Sign up to set email alerts
|

Persistent histone modifications at the BDNF and Cdk‐5 promoters following extinction of nicotine‐seeking in rats

Abstract: Drugs of addiction lead to a wide range of epigenetic changes at the promoter regions of genes directly implicated in learning and memory processes. We have previously shown that the histone deactylase inhibitor, sodium butyrate (NaB), accelerates the extinction of nicotine-seeking and provides resistance to relapse. Here we explore the potential molecular mechanisms underlying this effect. Rats received intravenous nicotine or saline self-administration, followed by six days of extinction training, with each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…To examine the persistence of elevated asBdnf-IV across extinction we assessed changes in gene expression following six days of extinction training compared to those that occur simply as a consequence of prior nicotine exposure (abstinence). This is the same time point at which we have previously observed decreases in H3K27 trimethylation and H3K9 dimethylation at the BDNF exon IV promoter (12). Rats underwent 12 days of selfadministration followed by 6 days of extinction training (Fig.…”
Section: Increased Asbdnf-iv Persists Across Abstinencementioning
confidence: 52%
See 3 more Smart Citations
“…To examine the persistence of elevated asBdnf-IV across extinction we assessed changes in gene expression following six days of extinction training compared to those that occur simply as a consequence of prior nicotine exposure (abstinence). This is the same time point at which we have previously observed decreases in H3K27 trimethylation and H3K9 dimethylation at the BDNF exon IV promoter (12). Rats underwent 12 days of selfadministration followed by 6 days of extinction training (Fig.…”
Section: Increased Asbdnf-iv Persists Across Abstinencementioning
confidence: 52%
“…We have previously shown that following 6 days of extinction from nicotine selfadministration, H3K27me 3 is decreased in the promoter region of Bdnf-IV (12), leading to the hypothesis that the Exon IV antisense transcript induces a permissive chromatin state in the rat IL (Fig. 7).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…An elegant study in mice demonstrated that nicotine increases expression of the Ash2l/Mef2c complex during cortical development, which subsequently leads to changes in histone methylation in the promoter region of glutamatergic synaptic genes and representative changes in dendritic spine number and branching (Jung et al, 2016 ). In rats, chronic nicotine exposure has also been associated with a decrease in methylation of several genes in the medial prefrontal cortex, orbitofrontal cortex, and NAcc (Mychasiuk et al, 2013 ; Castino et al, 2018 ). In the prefrontal cortex, nicotine self-administration was correlated with decreased histone methylation at the H3K27me3 and H3K9me2 marks in the BDNF and cyclin-dependent kinase 5 gene, but in contrast, withdrawal from nicotine elicited a decrease in H3K14 acetylation at the BDNF promoter (Castino et al, 2018 ), demonstrating different changes across stages of drug use.…”
Section: Further Considerations For Nicotine-mediated Changes In Genementioning
confidence: 99%